1988
DOI: 10.1080/0144341880080107
|View full text |Cite
|
Sign up to set email alerts
|

Peer Tutoring of Comprehension Strategies

Abstract: Four low achieving 12-year old readers were trained to tutor similar age low achieving readers in both general (monitoring) and specific (summarisation and illustration) for strategies reading comprehension. Repeated measures indicated that both tutors and tutees learned to use the strategies successfully. Use of both strategies enhanced comprehension for tutees. For tutors, there was evidence of generalisation of reading gains to their own reading. Gains made by tutors and tutees on two standardised reading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Peer mentoring and tutoring gained popularity as an intervention over two decades ago. Researchers (Cloward, 1976;Maxwell, 1994;Pickens & McNaughton, 1988;Strodtbeck, Ronchi, & Hansell, 1976) have concluded that the tutoring process has academic and psychological benefits to the tutor as well as the tutee. For instance, Cloward (1976) stated that "the tutor was the major beneficiary of the tutorial experience" (p. 227) in terms of academic gains.…”
Section: A Promising Prospect For Minoritymentioning
confidence: 99%
“…Peer mentoring and tutoring gained popularity as an intervention over two decades ago. Researchers (Cloward, 1976;Maxwell, 1994;Pickens & McNaughton, 1988;Strodtbeck, Ronchi, & Hansell, 1976) have concluded that the tutoring process has academic and psychological benefits to the tutor as well as the tutee. For instance, Cloward (1976) stated that "the tutor was the major beneficiary of the tutorial experience" (p. 227) in terms of academic gains.…”
Section: A Promising Prospect For Minoritymentioning
confidence: 99%
“…The findings of the present study are by no means unique. In a study by Pickens & McNaughton (1988), it was found that 12-year-old poor readers improved in comprehension and recall, but only minor improvements were detected in verbalized metacognitive knowledge, self-concept and attitude to reading. Dewitz et al (1987) report that fifth-graders who were taught comprehension monitoring improved in reading comprehension but their metacognitive awareness did not improve.…”
Section: Results and Discussion [1]mentioning
confidence: 92%
“…Vygotsky's ideas on the social mediation of strategic learning has resulted in a productive research orientation (e.g., Brown & Ferrara, 1985;Palincsar, 1986;Paris, 1986;Pickens & McNaughton, 1988). An application is the principle of scaffolded instruction.…”
Section: Teaching Comprehension Strategiesmentioning
confidence: 98%